Compaction behavior and consistency limits of laterite soil mixed with cement due to compaction delay - Zain Fauzi,; Rusdiansyah, (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Laterite soil, which is quite common in various places on Kalimantan Island, is generally used for road embankment material. However, laterite soil was often associated with road construction damage and landslides when used as a base embankment (subgrade) in Central Kalimantan. In order to overcome the issue, the handling process should be carried out by stabilizing laterite soil mixed with cement to ensure soil technical properties meet certain requirements. The time lag between soil-cement mixing stage, including the spreading and compaction time in the field caused by a damaged grader, compaction roller, heavy rain, bad weather, worker injuries, or other forms of disturbance, need to be evaluated. Therefore, this research used an experimental method to determine the effect of compaction delay on the behavior and consistency limits of Central Kalimantan laterite soil mixed with cement. The density behavior and cone limits were determined by mixing laterite soil with variations in cement content of 2%, 4%, 6%, 8%, and 10% to obtain an increased dry weight value of 1.39 t/m3 to 1.43 t/m3. Compaction process was postponed for 1, 2.5, and 4 hours, respectively. In conclusion, Liquid Limit (LL) decreased with increase in cement content, while Plasticity Index (PI) reduced with rise in cement content, and increased with a delay in compaction time of 1, 2.5, and 4 hours.